2003
DOI: 10.1038/emm.2003.31
|View full text |Cite
|
Sign up to set email alerts
|

A model for the reaction mechanism of the transglutaminase 3 enzyme

Abstract: A bstractTransglutam inase enzym es (TG ases) catalyze the calcium dependent formation of an isopeptide bond betw een protein-bound glutam ine and lysine substrates. Previously w e have show n that activated TG ase 3 acquires tw o additional calcium ions at site tw o and three. The calcium ion at site three results in the opening of a channel. A t this site, the channel opening and closing could m odulate, depending on which m etal is bound. Here we propose that the front of the channel could be used by the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
0
33
0
2
Order By: Relevance
“…maintained in low (0.09 mM) calcium-containing medium. This is surprising, because calcium is required for transglutaminase activity (89,90). Our present and past (25,26) findings suggest that TG1 can be activated without an increase in intracellular calcium.…”
Section: Figure 8 Tg1-flag(c377a) Accumulates In Aggresomesmentioning
confidence: 62%
“…maintained in low (0.09 mM) calcium-containing medium. This is surprising, because calcium is required for transglutaminase activity (89,90). Our present and past (25,26) findings suggest that TG1 can be activated without an increase in intracellular calcium.…”
Section: Figure 8 Tg1-flag(c377a) Accumulates In Aggresomesmentioning
confidence: 62%
“…Moreover, we have shown that an increase in Mg 2ϩ ion concentrations alone, even without GTP, can inhibit the enzyme, raising the possibility that GTP binding and Mg 2ϩ ion substitution at site 3 represent a coordinated event in the inactivation of TGase 3 (28). A set of concerted changes in the enzyme structure, stemming from the binding of GTP and Mg 2ϩ ion, cause the closing of the channel required for substrate access to the active site (47). Thus, the GTP␥S imparts the inactive state through a set of local structural rearrangements and not through its direct occlusion of the active site.…”
mentioning
confidence: 97%
“…Furthermore, it has been proposed that the front of the channel could be used by the two substrates for enzyme reaction (47), based on detailed analyses of current structural information on the zymogen and the activated forms of TGase 3. Therefore, we examined the crystal structures in the presence of GTP␥S versus GDP in terms of their implications for substrate access to the active site residues including Cys 272 .…”
mentioning
confidence: 99%
“…Whereas the γ′ peptide-IIa interface has been localized to ABE-II, the binding site for GpIbα is more ambiguous and may be at ABE-II or ABE-I. The C-terminal tail of GpIbα (269)(270)(271)(272)(273)(274)(275)(276)(277)(278)(279)(280)(281)(282)(283)(284)(285)(286) shares similar sequence elements with the γ′ peptide. Both GpIbα X-ray structures (96,97) display comparable ABE-II interactions for the C-terminal tail; however, the Celikel structure (1OOK) shows the C-terminal tail dimerizing thrombin through binding with ABE-I in a symmetry related thrombin molecule (97).…”
Section: Gpibα Peptide (269-286) Binding To Thrombinmentioning
confidence: 99%
“…At the present time, a peptide-based anticoagulant that targets ABE-II has not been developed. By examining the conformational features associated with γ′ peptide (410-427) and GpIbα (269)(270)(271)(272)(273)(274)(275)(276)(277)(278)(279)(280)(281)(282)(283)(284)(285)(286) binding to ABE-II, an ABE-II targeting peptide with anticoagulant properties may be developed employing the unique structural elements characteristic of these complexes.…”
Section: Research Goalsmentioning
confidence: 99%